Enhancement of Energy Efficiency and Food Product Quality Using Adsorption Dryer with Zeolite - Djaeni, Moh; Sasongko, S.B.; van Boxtel, A.J.B. (Center of Biomass & Renewable Energy, Diponegoro University, 2013)
Drying is a basic operation in wood, food, pharmaceutical and chemical industry. Currently, several drying methods are often not efficient in terms of energy consumption (energy efficiency of 20-60%) and have an impact on product quality degradation due to the introduction of operational temperature upper 80oC. This work discusses the development of adsorption drying with zeolite to improve the energy efficiency as well as product quality. In this process, air as drying medium is dehumidified by zeolite. As a result humidity of air can be reduced up to 0.1 ppm. So, for heat sensitive products, the drying process can be performed in low or medium temperature with high driving force. The study has been conducted in three steps: designing the dryer, performing laboratory scale equipment (tray, spray, and fluidised bed dryers with zeolite), and evaluating the dryer performance based on energy efficiency and product quality. Results showed that the energy efficiency of drying process is 15-20% higher than that of conventional dryer. In additon, the dryer can speed up drying time as well as retaining product quality.